Answer:
x = - 3 ±
![√(10)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/v9fk9je1zoywmssyv96nieje565m5yyay1.png)
Explanation:
Given
4x² + 24x = 4 ( divide through by 4 )
x² + 6x = 1
To complete the square
add ( half the coefficient of the x- term )² to both sides
x² + 2(3)x + 9 = 1 + 9
(x + 3)² = 10 ( take the square root of both sides )
x + 3 = ±
( subtract 3 from both sides )
x = - 3 ±
![√(10)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/v9fk9je1zoywmssyv96nieje565m5yyay1.png)